Bone Mineral Density in Patients Receiving Anticonvulsant Drugs - Kadir Yıldırım; Kazım Şenel; Mahir Uğur; Akın Erdal; Saliha Karatay (Galenos Yayinevi, 2002)
The study was carried out to determine possible effects of anticonvulsant drugs on bone mineral density. Twenty two patients with epilepsy who have been receiving anticonvulsant drugs and also 22 healthy controls were included in the study. The average age was 28.9 ± 8.9 years in the patients group and 30.5 ± 6.9 years in the control group. The average drug receiving time was 6.45 ± 4.2 years. At baseline ESR, hemogram, urine deoxypiridinoline (DPD), routine biochemical and hormonal values were determined in both groups. Lumbar spine and left femur bone mineral density (BMD) values were determined with hologic 2000 DEXA. In the statistical analysis, urine DPD levels in the patient group were significantly higher than control group (p<0.001). There wasn't any statistically difference in the other blood parameters between two groups (p>0.05). Lumbar spine and left femur BMD values were significantly decreased in patients group (respectively p<0.01, p<0.001). We determined that in the patients using anticonvulsant drugs there was an increase in bone resorption and this effect was more evident in cortical bone than trabecular bone.